Distal chromosome 16p11.2 duplications containing SH2B1 in patients with scoliosis. Issue 7 (25th February 2019) - Sadler, Brooke; Haller, Gabe; Antunes, Lilian; Bledsoe, Xavier; Morcuende, Jose; Giampietro, Philip; Raggio, Cathleen; Miller, Nancy; Kidane, Yared; Wise, Carol A; Amarillo, Ina; Walton, Nephi; et al.
Abstract : Introduction: Adolescent idiopathic scoliosis (AIS) is a common musculoskeletal disorder with strong evidence for a genetic contribution. CNVs play an important role in congenital scoliosis, but their role in idiopathic scoliosis has been largely unexplored. Methods: Exome sequence data from 1197 AIS cases and 1664 in-house controls was analysed using coverage data to identify rare CNVs. CNV calls were filtered to include only highly confident CNVs with >10 average reads per region and mean log-ratio of coverage consistent with single-copy duplication or deletion. The frequency of 55 common recurrent CNVs was determined and correlated with clinical characteristics. Results: Distal chromosome 16p11.2 microduplications containing the gene SH2B1 were found in 0.7% of AIS cases (8/1197). We replicated this finding in two additional AIS cohorts (8/1097 and 2/433), resulting in 0.7% (18/2727) of all AIS cases harbouring a chromosome 16p11.2 microduplication, compared with 0.06% of local controls (1/1664) and 0.04% of published controls (8/19584) (p=2.28×10 −11, OR=16.15). Furthermore, examination of electronic health records of 92 455 patients from the Geisinger health system showed scoliosis in 30% (20/66) patients with chromosome 16p11.2 microduplications containing SH2B1 compared with 7.6% (10/132) of controls (p=5.6×10 −4, OR=3.9). Conclusions: Recurrent distal chromosome 16p11.2 duplications explain nearly 1% of AIS. Distal chromosome 16p11.2 duplications may contribute to scoliosis pathogenesis by directly impairing growth or by altering expression of nearby genes, such as TBX6 . Individuals with distal chromosome 16p11.2 microduplications should be screened for scoliosis to facilitate early treatment.